Задача перевантаження контейнерів безпосередньо між потягами - Калайда, Н. С. (ХНУРЕ, 2019)
Intermodal container transportations today are an efficient and reliable way of cargo transportation. Container transportation by rail is a significant part of intermodal transportation so, it is necessary to optimize the processes of cargo handling. Immediate containers transshipment between trains problem is considered to optimize the process of container reloading.